Enzymatic synthesis of the modified mycotoxins 3-lactyl- and 3-propionyl-deoxynivalenol - Michlmayr, Herbert; Wiesenberger, Gerlinde; Twaruschek, Krisztian; Kastner, Florian; Sopel, Marta M.; Hametner, Christian; Berthiller, Franz; Adam, Gerhard (Frontiers in Sustainable Food Systems, 2024)
The use of lactic acid bacteria as a low-cost sustainable management tool to prevent further build-up of Fusarium mycotoxins during grain storage is increasingly propagated. It has been reported that even deoxynivalenol contamination already formed in the field can be reduced by such treatment in unknown ways. An enigmatic deoxynivalenol derivative, 3-lactyl-deoxynivalenol, has been reported already in 1982 as the toxic principle of Fusarium-infected barley from China, but very little is known about this metabolite. Here, we show that the enzymatic machinery of Fusarium graminearum is sufficient for its biosynthesis. Similarly, when challenged with propionic acid, F. graminearum can form a novel modified mycotoxin, 3-propionyl-deoxynivalenol. Lactic acid and propionic acid are first converted into lactyl-CoA and propionyl-CoA, respectively. These acyl-CoA derivatives can subsequently be used by the 3-O-acyltransferase encoded by TRI101. We expressed the respective genes in E. coli and utilized the affinity-purified proteins for enzymatic synthesis of the reference substances 3-lactyl- and 3-propionyl-deoxynivalenol. The structures of the purified compounds were confirmed by nuclear magnetic resonance spectroscopy. Preliminary toxicological assessment using in vitro translation assays indicated residual toxicity, most likely due to reactivation of deoxynivalenol by de-acylation. In conclusion, this study reports a method to synthesize 3-lactyl- and 3-propionyl-deoxynivalenol reference substances, which will be highly useful to determine occurrences of these acylated deoxynivalenol-derivatives in cereal samples and to perform more detailed studies to evaluate their toxicological relevance.